MANAJEMEN PENGELOLAAN PARIWISATA DI KABUPATEN KEPULAUAN TALAUD - BAGUNDA, NOVLYN; TULUSAN, FEMMY; LALOMA, ALDEN (JURNAL ADMINISTRASI PUBLIK, 2019)
This research focuses on tourism management, namely planning, organizing, mobilizing andmonitoring tourism activities carried out by the Regional Government of Talaud Islands Regency.The aim is to be studied because of the management implemented by the Talaud Islands DistrictGovernment. The research method used in this study is a qualitative method with data collectiontechniques with triangulation (combined).Talaud Regency starts with the village Musrembang,subdistrict Musrembang, and district Musrembang. Work distribution is also available for eachindividual and their respective fields in accordance with their duties. In carrying out its activities, itwas agreed on the rules and technical instructions. Then the Non-Governmental Organization(NGO), the village government and the community themselves.Keywords: Management, Tourism